2022
DOI: 10.1002/ejoc.202200042
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Nickel‐Catalyzed N‐Allylation of C3‐Unprotected Indoles under Mild and Clean Conditions

Abstract: A simple salt free and selective N‐allylation of indoles with allylic alcohols has been developed. The protocol uses a catalytic amount of a nickel complex generated in situ from Ni(cod)2 and dppf as diphosphine. The use of DMSO as the reaction solvent is crucial to control the regioselectivity of the reaction with the exclusive formation of the N‐allyl product among up to three possible products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…We were able to perform a glovebox‐free setup of the reaction using 5 and isolate 13 in 87 % yield. In another example, we found that Ni(COD)(DQ) performed poorly in the N ‐allylation of indole reported by Sauthier and co‐workers but that complex 7 resulted in high yield of desired product 14 [39] . Complexes 5 and 8 also outperformed Ni(COD)(DQ) in this reaction, and 7 could be used outside of the glovebox to prepare 14 in 62 % isolated yield.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…We were able to perform a glovebox‐free setup of the reaction using 5 and isolate 13 in 87 % yield. In another example, we found that Ni(COD)(DQ) performed poorly in the N ‐allylation of indole reported by Sauthier and co‐workers but that complex 7 resulted in high yield of desired product 14 [39] . Complexes 5 and 8 also outperformed Ni(COD)(DQ) in this reaction, and 7 could be used outside of the glovebox to prepare 14 in 62 % isolated yield.…”
Section: Resultsmentioning
confidence: 76%
“…In another example, we found that Ni(COD)-(DQ) performed poorly in the N-allylation of indole reported by Sauthier and co-workers but that complex 7 resulted in high yield of desired product 14. [39] Complexes 5 and 8 also outperformed Ni(COD)(DQ) in this reaction, and 7 could be used outside of the glovebox to prepare 14 in 62 % isolated yield. Morandi and co-workers reported that the combination of Ni(COD) 2 and DCYPE catalyzes the amination of thioethers in the presence of the strong base LiHMDS.…”
Section: Evaluation Of Catalytic Performancementioning
confidence: 91%
“…Before performing the tandem reaction, we started with the optimization of the nickel catalyzed allylation reaction of benzoin 1 a with allyl alcohol 2 a . The first test was realized in DMSO, which proved to be a good solvent for the N ‐allylation of indoles, [25] in the presence of 1.5 mol% Ni(cod) 2 as nickel source and dppf (diphenylphosphinoferrocene) ligand at 70 °C (Table 1 and Scheme 2). Nevertheless, the reaction did not occur (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…In order to prevent waste, allyl alcohol is used as an allylation reagent leading to water as the sole reaction by-product. [35][36][37][38][39] It is also noteworthy that allyl alcohol is industrially produced 40 and is also accessible from vegetal feedstock as glycerol. [41][42][43][44] Depending on the sites that are allylated and the substitution degree, several products are accessible.…”
Section: Introductionmentioning
confidence: 99%